2018
DOI: 10.3389/fnut.2018.00085
|View full text |Cite
|
Sign up to set email alerts
|

The Hop Polyphenols Xanthohumol and 8-Prenyl-Naringenin Antagonize the Estrogenic Effects of Fusarium Mycotoxins in Human Endometrial Cancer Cells

Abstract: The Fusarium toxin zearalenone (ZEN) and its reductive metabolite α-zearalenol (α-ZEL) are well-documented endocrine disruptors that are frequently found to contaminate cereal products, including beer. But also hop is known to represent a source for endocrine active compounds, containing amongst others xanthohumol (XAN), which might be converted to the potent phytoestrogen 8-prenylnaringenin (8-PN). In the present study, we investigated the interaction of these xenoestrogens in mixtures which might occur in be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…To assess interactions that do not follow a linear dose–response relationship, mathematical models must be applied to calculate this “additive effect”. Chou’s “multiple drug effect equation” (Chou 2006) is currently recognized as the most accurate model existing to describe these effects (Aichinger et al 2018; Alassane-Kpembi et al 2017; Vejdovszky et al 2017). However, the determination of an IC 50 value and, therefore, a measurable effect of at least 50% is a prerequisite for the application of this model.…”
Section: Methodsmentioning
confidence: 99%
“…To assess interactions that do not follow a linear dose–response relationship, mathematical models must be applied to calculate this “additive effect”. Chou’s “multiple drug effect equation” (Chou 2006) is currently recognized as the most accurate model existing to describe these effects (Aichinger et al 2018; Alassane-Kpembi et al 2017; Vejdovszky et al 2017). However, the determination of an IC 50 value and, therefore, a measurable effect of at least 50% is a prerequisite for the application of this model.…”
Section: Methodsmentioning
confidence: 99%
“…The activity of AlP after 48 h of incubation was determined as a measure for ER activation as recently described (Aichinger et al 2018a). In brief, we used assay medium to seed 10,000 cells/well into 96-well plates.…”
Section: Alkaline Phosphatase (Alp) Assaymentioning
confidence: 99%
“…Similarly to soybeans, hops used to produce beer is characterized by the presence of some prenylflavonoids (e.g., naringenin, 8-prenylnaringenin, 6-prenylnaringenin, 6,8-diprenylnaringenin, and 8-geranylnaringenin) that are potent phytoestrogens with a dual effect being able to bind both estrogen receptor isoforms and to inhibit specific enzymes involved in the estrogenic cellular responses [124,125]. In this context, Aichinger et al [126] demonstrated the ability of the phytoestrogens from hops xanthohumol and 8-prenylnaringenin to antagonize the estrogenic effects of the Fusarium mycotoxins ZEN and α-ZEL. Therefore, possible interactions can be expected also in combination with the estrogenic Alternaria toxins AOH and AME.…”
Section: The Key Role Of Bioactive Compoundsmentioning
confidence: 99%